Analysis of Service Quality at the Regional Financial and Asset Management Office of South Bengkulu Regency - Gustini Gustini (Penerbit Jurnal Indonesia, 2022)
Public services by government officials in various service sectors related to the fulfillment of civil rights and basic needs are considered not in accordance with the demands and expectations of the community. This can be seen, among others, from the number of complaints, complaints submitted by the public through the media or directly to the ministry. For this reason, it is necessary to assess the community as a public service by users of these services. The purpose of this study was to analyze the quality of services provided by the Department of Financial and Asset Management in South Bengkulu Regency. This study was designed as a descriptive study. The population in this study is all people who carry out activities in the field of the Regional Financial and Asset Management Office of South Bengkulu Regency. The sample in this study were 150 respondents. The data collection technique in this study was a questionnaire. Data were analyzed using the Value of Society Satisfaction Index (SSI). The results showed that: The overall measurement of the Community Satisfaction Index (ISIS) value showed positive things and was categorized in good and good condition.